2009
DOI: 10.1387/ijdb.082690mv
|View full text |Cite
|
Sign up to set email alerts
|

Role of polycomb proteins Ring1A and Ring1Bin the epigenetic regulation of gene expression

Abstract: Generation of cell diversity depends on epigenetic regulatory mechanisms. Polycomb group (PcG) proteins are central components of epigenetic regulation in metazoans. The system, initially associated with transcriptional program stability during development, is also involved in the regulation of other processes, such as maintenance of stem cell pluripotency and cell proliferation. PcG regulation involves chromatin modifications through covalent histone modifications. One of these modifications, the monoubiquity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 155 publications
(259 reference statements)
1
53
1
1
Order By: Relevance
“…However, the mechanism of Rnf2 in cancer development remains poorly understood. Previously, Rnf2 was shown to repress the transcription of p16Ink4a, which mediates Rnf2 activities in cancer cells 22,33,34). However, in the present study, Rnf2 directly degraded p53 through the proteasome pathway.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, the mechanism of Rnf2 in cancer development remains poorly understood. Previously, Rnf2 was shown to repress the transcription of p16Ink4a, which mediates Rnf2 activities in cancer cells 22,33,34). However, in the present study, Rnf2 directly degraded p53 through the proteasome pathway.…”
Section: Discussioncontrasting
confidence: 65%
“…The gene regulation through PC complexes involves the trimethylation of histone H3 at lysine 27 catalyzed through the activity of PRC2 (20), which in turn recruits the PRC1 complex to chromatin to mediate histone H2A monoubiquitination (21). As the primary E3 ligase responsible for H2A modification in the PRC1 complex, Rnf2 plays important roles in both early development and ES cell maintenance (22). In addition to its monoubiquitination activity, the PRC1 complex also has poly-ubiquitination activity.…”
mentioning
confidence: 99%
“…In addition, Ring1b can participate in several PRC1-like complexes (Gao et al, 2012) and PRC1 can be found at chromatin independently of PRC2 (Trojer et al, 2011). Two orthologs of the Drosophila E3 ligase dRing, Ring1a and Ring1b, are found in mammals and amphibians, whereas only a single gene that is most homologous to Ring1b has been identified in zebrafish (Le Faou et al, 2011;Vidal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PRC2 catalyzes the methylation of H3K27; the methylation of H3K27, particularly trimethylation, is the main hallmark of PcG-mediated silencing (Levine et al, 2004;Ringrose et al, 2003), which occurs through enzymatic activity (in association with PRC1). In addition to the nonenzymatic chromatin-compacting regulatory effect of PRC1 (Eskeland et al, 2010), this Pc complex is able to ubiquitylate histone H2A through Ring1A and Ring1B (for reviews, see Eckert et al, 2011;Richly et al, 2011;Vidal, 2009).…”
Section: Golbabapour Et Almentioning
confidence: 99%